Purification of Self‐Assembled DNA Tetrahedra Using Gel Electrophoresis. Issue 9 (16th September 2022) - Patel, Akul; Valsangkar, Vibhav; Halvorsen, Ken; Chandrasekaran, Arun Richard
Abstract: DNA nanostructures have found applications in a variety of fields such as biosensing, drug delivery, cellular imaging, and computation. Several of these applications require purification of the DNA nanostructures once they are assembled. Gel electrophoresis–based purification of DNA nanostructures is one of the methods used for this purpose. Here, we describe a step‐by‐step protocol for a gel‐based method to purify self‐assembled DNA tetrahedra. With further optimization, this method could also be adapted for other DNA nanostructures. © 2022 Wiley Periodicals LLC. Basic Protocol : Purification of self‐assembled DNA tetrahedra